Pengaruh Kepercayaan Masyarakat Dalam Mendorong Minat Menabung di Bank Syariah (Studi Kasus: Masyarakat Kelurahan Putat Jaya Kecamatan Sawahan Kota Surabaya) - Firmansyah, Achmad Kharis; Mawardi, Imam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of financial institutions, especially in Indonesia, has grown quite rapidly. This is proven by the many financial institutions that have been established in Indonesia, ranging from micro to macro scale, one of which is the Islamic Financial Institution. Islamic banking is a financial institution that acts as an intermediary in collecting and distributing funds to the community in accordance with sharia principles and is sourced from the verses of the Qur'an and As-Sunnah, some of which are related to Muamalah and ethics of financial transactions. This study aims to determine: 1.) how much trust the people of Putat Jaya Village, Sawahan District, Surabaya City have in saving at Islamic Banks. 2.) To determine the factors that influence the interest of the people of Putat Jaya Village, Sawahan District, Surabaya City to save at Islamic Banks. 3.) To foster the trust of the people of Putat Jaya Village, Sawahan District, Surabaya City in saving at Islamic Banks. The type of research is research with a quantitative approach. This study uses simple regression analysis, data collection methods with observation, questionnaires and data analysis methods, namely, data quality testing and hypothesis testing. The results of this study indicate that all of the hypotheses proposed have been proven to be true, namely the calculated value of public trust of 30,669, this value is known to be greater than the table value of 1,660, the significance level is 0.000 0.05. Given that the calculation table, it shows that H0 is rejected and H1 is accepted, which means that the variable of public trust has an effect on the interest in saving at Islamic Banks. Therefore, it is hoped that the people of Putat Jaya Village will always prioritize Islamic financial institutions for transactions, especially in saving activities.